Pengetahuan tentang Thalasemia Hubungannya dengan Tingkat Kecemasan Ibu yang Memiliki Anak Thalasemia - Susan Susyanti; Restu Prayustira (Jurnal Medika Cendikia, 2016)
Diseases blood disorders, namely Thalassemia is a blood disorder characterized by the existence of conditions that are easily damaged erythrocytes and shorter-lived (<120 days). Indonesia is one of the countries included in circumference with a prevalence of Thalassemia Thalassemia gene carriers is quite high by 5-10%. The number of cases of Thalassemia child that ends with the death would cause anxiety for parents, in this case the mother. This is mainly due to the lack of understanding about the management of thalassemia mother due to lack of knowledge. The purpose of this study was to determine the relationship of knowledge to the level of anxiety mothers of children with Thalassemia. To achieve these objectives, implemented quantitative descriptive research with cross sectional approach, samples taken as many as 78 people. The result showed more than half of respondents (55.2%) have less knowledge about Thalassemia; anxiety levels were found in almost half of the respondents (42.3%); there is a significant relationship between mother's knowledge about Thalassemia with anxiety levels mothers of children with thalassemia (p-value = 0.000 <α = 0.05). It is expected to nurse the child must increase efforts to provide information about Thalassemia so that the parents can be better prepared and able to accept the conditions of children in all likelihood that will happen in the future.